Effect of branched-chain amino acid supplements on muscle strength and muscle mass in patients with liver cirrhosis. Issue 12 (December 2017) - Uojima, Haruki; Sakurai, Seiko; Hidaka, Hisashi; Kinbara, Takeshi; Sung, Ji Hyun; Ichita, Chikamasa; Tokoro, Shinnosuke; Masuda, Sakue; Sasaki, Akiko; Koizumi, Kazuya; Egashira, Hideto; Kako, Makoto; et al.
Abstract : Objective: The aim of this study was to assess the effect of branched-chain amino acid (BCAA) supplements on muscle strength and muscle mass in patients with liver cirrhosis. Patients and methods: We carried out a single-center, prospective study of adult cirrhotic patients receiving nutrition therapy at Shonan Kamakura General Hospital. A 28-day pretreatment observation period was followed by a 24-week treatment period. Patients who fulfilled the treatment criteria received one package of oral BCAA supplement powder twice a day and the response was evaluated. A responder to BCAA in muscle strength and muscle mass was defined as a patient with an increased skeletal muscle mass index and hand grip assessed 24 weeks after drug treatment commenced. Results: Eighty-two patients fulfilled our criteria and completed the treatment. In terms of muscle strength, there were 59 (72.0%) responders to BCAA supplementation with a significant increase in hand grip from before treatment (22.2±6.3 kg) to after treatment (23.9±6.4 kg) ( P <0.001). In terms of muscle mass, 36 (43.9%) patients responded to BCAA with a slight decrease in skeletal muscle mass index from before treatment (7.40±1.62) to after treatment (7.30±1.49) ( P =0.333). Conclusion: BCAA supplementation improved low muscle strength in patients with chronic liver disease, but did not increase muscle mass during the treatment period.